Ventricular tachycardia ablation before an implantable cardioverter defibrillator in secondary prevention: is always the best option?. (3rd October 2022) - Martinho, A; Almeida, J; Antonio, N; Elvas, L; Goncalves, L
Abstract: Background: Among patients with an aborted episode of malignant ventricular arrhythmias without a reversible cause, the Implantable Cardioverter Defibrillator (ICD) is considered an important therapy for secondary prevention of sudden cardiac death (SCD). Some authors propose primary catheter ablation and deferred ICD implantation may be the preferred approach in patients with substrate-related ventricular tachycardia. Purpose: We want to evaluate the need of secondary time ablation in patients with secondary prevention ICD, when submitted only a medical therapy after the index event. Methods: We conducted a retrospective, observational study of 90 patients who consecutively implanted ICD after an aborted episode of malignant ventricular arrhythmias without a reversible/known cause between 2014 and 2020. Patients with Brugada Syndrome, Wolff-Parkinson-White syndrome, QT related diseases and previous ventricular tachycardia (VT) ablation were excluded. Baseline clinical characteristics were analyzed, and a 1-year follow-up was performed: cardiovascular (CV) death, sustain VT), ventricular fibrillation (VF), antitachycardia pacing (ATP), ICD shock, VT ablation. Results: Mean age was 58±18 years, 80% (n=72) were male and 65.5% (n=59) had a non-ischemic etiology. Most of the patients (61%; n=56) present with hemodynamic unstable VT or syncope, and 38% (n=34) with SCD [most due to VF (n=30)]. After the index event 41.1% (n=37) and 83.8% (n=75) initiate antiarrhythmic and beta-blocker (BB), respectively. During 1-year follow-up (FUP) 11.1% (n=10) had a sustain VT and 2.2% (n=2) VF leading to ATP and appropriated shock in 11.1% (n=10) and 10% (n=9), respectively. There was 2 CV death [due to acute heart failure (HF)], 8 HF hospitalization and 3 VT ablation during follow-up. The presence of chronic kidney disease at baseline was the only parameter related to 1-year CV death (1.3% vs 18.2%, p=0.039) and HF hospitalization (0% vs 18.2%, p=0.014). The antiarrhythmic after index event was associated with a significant less sustain VT [10% vs 45%, OR 0.114 (IC 95% 0.014 to 0.927] and consequently ATP (adjusted for age) and had a numerical benefit in ICD shock (2.7% vs 15.1%, p=0.076) and need of a secondary time ablation (0% vs 5.7%, p=0.266). Conclusion: The ICD implant with antiarrhythmic therapy, as a primary approach to secondary prevention (vs ablation), after an aborted episode of malignant ventricular arrhythmias still showed to be a secure and viable first option. Funding Acknowledgement: Type of funding sources: None.